2021
DOI: 10.1016/j.ekir.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Workweek Study: Risk Factors for Daily Changes in Creatinine

Abstract: Introduction: Agricultural workers laboring in thermally stressful environments are at increased risk for kidney injury and chronic kidney disease of unknown origin (CKDu), and their environmental and occupational exposures have been considered to be important risk factors. This study examined the effects of repeated kidney stress from the simultaneous strain of work and other factors experienced by workers in Guatemala during a typical workweek.Methods: We collected data from 107 sugarcane workers across 7 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Patients typically present with CKD stage 3 or 4, although an acute presentation has been reported with fever, vomiting, and headaches [15,18,19]. In Central America, transiently increased blood pressure with an elevated serum creatinine level during active farm work has been associated with subsequent kidney functional decline and CKDu [20]. In Indian CKDu patients, hypertension was seen in 53.9%, although cardiovascular complications were found in only 18% [7 & ].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients typically present with CKD stage 3 or 4, although an acute presentation has been reported with fever, vomiting, and headaches [15,18,19]. In Central America, transiently increased blood pressure with an elevated serum creatinine level during active farm work has been associated with subsequent kidney functional decline and CKDu [20]. In Indian CKDu patients, hypertension was seen in 53.9%, although cardiovascular complications were found in only 18% [7 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…In Mexico, agrochemicals have been potentially associated with impaired kidney function and proteinuria [29]. Drinking from clean tank vs. municipal or well water lowers urinary arsenic, lead, uranium, and glyphosate concentrations and protects against increased serum creatinine [20]. High urine cadmium and arsenic negatively associate with estimated glomerular filtration rate (eGFR) ( r = −4.23 and −4.36, respectively) while cadmium is positively associated with urinary NGAL (r=2.92) [30].…”
Section: Pathogenesismentioning
confidence: 99%
“…In 18 studies, wet bulb globe temperature (WBGT) index was calculated [12-14, 17, 18, 21, 22, 24, 25, 30-38]; 15 of these articles used the WBGT meter [12,14,17,18,21,22,25,[30][31][32][33][35][36][37][38]. In two of these studies, the index values were obtained from the safety engineering department [13,24], and in another study, the temperature and relative humidity were measured using a digital weather meter [34].…”
Section: Prospective Cohort Studiesmentioning
confidence: 99%
“…The median and IQR of postpre shift difference of eGFR among non-AKI and AKI workers was -14.60 (-18.60, -8.25) and -43.10 (-52.30, -34.88), respectively [39]. An investigation across seven consecutive work shifts found that increased WBGT was associated with increased SCr across the shift on all seven workdays (regression coefficient= 2.5%, p-value= 0.02) [14].…”
Section: Serum Creatinine and Egfrmentioning
confidence: 99%
See 1 more Smart Citation